Cooperative advertising and ordering policies in a two-echelon supply chain with risk-averse agents. (March 2018) - Zhou, Yong-Wu; Li, Jicai; Zhong, Yuanguang
Highlights: Investigating a cooperative advertising problem mixed with production/ordering planning. Considering the agents in the supply chain have different risk attitudes. Measuring the agents' risk through the CVaR approach. Revealing the effect of demand uncertainty and the two agents' risk aversion. Abstract: This paper considers a cooperative advertising and ordering issue in a two-echelon supply chain in which a risk-averse manufacturer sells a product through a risk-averse retailer. We assume that demand for the product is a random variable influenced by the manufacturer's global advertising and the retailer's local advertising. To stimulate demand for the product, the risk-averse manufacturer induces the risk-averse retailer to increase local advertising expenditure through cooperative advertising contracts. With the objective of maximizing conditional value-at-risk, models for determining the retailer's optimal order quantity and both agents' advertising investments are developed for both centralized and decentralized settings. We reveal the effect of demand uncertainty and two agents' risk aversion on both agents' optimal advertising/ordering policies. Through both theoretical and numerical analyses, we find that: 1) the centralized scenario may perform worse than the decentralized one in many cases if the decision-maker of the centralized supply chain is more risk averse than its two participants; 2) whether the risk-averse manufacturer is willing to share the retailer's local advertising expenditure depends significantly on the degree of two agents' risk aversion; and 3) in the decentralized setting, it will be more beneficial for both agents that the leader is more risk averse than the follower. These new findings are further supplements to the results in the existing related literature.